2023
DOI: 10.2147/ijgm.s411122
|View full text |Cite
|
Sign up to set email alerts
|

Total T Cell Density and Expression of T Memory Stem Cell Markers are Associated with Better Prognosis in Colon Cancer

Abstract: Background: Immune checkpoint inhibitors have achieved limited clinical effectiveness in colon cancer. Stem memory T cells (TSCMs) and in-situ cytotoxic T cells are dominant contributors to host immunity. Currently, data on the correlation between TSCM and T cell abundance and clinicopathological characteristics in colon cancer are largely unavailable. Methods: In-situ cytotoxic T cells are identified based on the quantification of CD3 + and CD8 + markers using immunohistochemistry (IHC) in the core of the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…5,6 In the present study, we clearly We also found that NPC patients with CD27-positive TILs exhibited better survival than patients without such cells. Consistent with our findings, recent studies by other researchers showed a correlation between the presence of CD27-positive TILs and a favorable prognosis in some solid tumors, [28][29][30] suggesting that CD27-positive immune cells may include lymphocytes capable of eliciting antitumor immune responses, such as tumor-specific cytotoxic and helper T cells.…”
Section: Discussionsupporting
confidence: 92%
“…5,6 In the present study, we clearly We also found that NPC patients with CD27-positive TILs exhibited better survival than patients without such cells. Consistent with our findings, recent studies by other researchers showed a correlation between the presence of CD27-positive TILs and a favorable prognosis in some solid tumors, [28][29][30] suggesting that CD27-positive immune cells may include lymphocytes capable of eliciting antitumor immune responses, such as tumor-specific cytotoxic and helper T cells.…”
Section: Discussionsupporting
confidence: 92%